Flavonoids from leaves of Derris urucu: assessment of potential effects on seed germination and development of weeds - SILVA, Ewerton Afonso Silva da (2014)
In some previous studies, we described the isolation of nine compounds from leaves of Derris urucu, a species found widely in the Amazon rainforest, identified as five stilbenes and four dihydroflavonols. In this work, three of these dihydroflavonols [urucuol A (1), urucuol B (2) and isotirumalin (3)] were evaluated to identify their potential as allelochemicals, and we are also reporting the isolation and structural determination of a new flavonoid [5,3′-dihydroxy-4′-methoxy-(7,6:5″,6″)-2″,2″-dimethylpyranoflavanone (4)]. We investigated the effects of the dihydroflavonols 1-3 on seed germination and radicle and hypocotyl growth of the weed Mimosa pudica, using solutions at 150 mg.L–1. Urucuol B, alone, was the substance with the greatest potential to inhibit seed germination (26%), while isotirumalin showed greater ability to reduce the development of the hypocotyl (25%), but none of the three substances showed the potential to inhibit radicle. When combined in pairs, the substances showed synergism for the development of root and hypocotyl and effects on seed germination that could be attributed to antagonism. When tested separately, the trend has become more intense effects on seed germination, while for the substances tested in pairs, the intensity of the effect was greater on development of weed.